Integrative transcriptional and metabolic analyses provide insights into cold spell response mechanisms in young shoots of the tea plant. (23rd April 2018) - Hao, Xinyuan; Tang, Hu; Wang, Bo; Yue, Chuan; Wang, Lu; Zeng, Jianming; Yang, Yajun; Wang, Xinchao
Abstract: Green tea has attracted an increasing number of consumers worldwide due to its multiple health benefits. With the increase in global warming, more frequent cold spells in the spring often cause more serious damage to green tea production because of the young leaves used. We recorded the changes in climatic conditions during a typical cold spell and the damage symptoms caused by the cold spell in different tea cultivars and breeding lines. By simulating the low temperature of a cold spell under controlled conditions, comparative transcriptome and metabolic analyses were performed with sprouting shoots. Many pathways and genes were regulated differentially by the cold spell conditions. Taking into account the metabolic analysis, the results suggested that the mitogen-activated protein kinase (MAPK)-dependent ethylene and calcium signalling pathways were two major early cold-responsive mechanisms involved in sprouting shoots and were followed by the induction of the Inducer of CBF Expressions (ICE)-C-repeat binding factors (CBF)-cold-responsive (COR) signalling pathway to augment cold tolerance. During the cold shock, growth, photosynthesis and secondary metabolism—mainly involving flavonoid biosynthesis—were remarkably affected. Notably, the increased starch metabolism, which might be dependent on the high expression of β-amylase3 ( BAM3 ) induced by CBF, played crucial roles in protecting young shoots against freezing cold. A schematic diagram of cold spell response mechanisms specifically involved in the sprouting shoots of the tea plant is ultimately proposed. Some essential transcriptional and metabolic changes were further confirmed in the plant materials under natural cold spell conditions. Our results provide a global view of the reprograming of transcription and metabolism in sprouting tea shoots during a cold spell and meaningful information for future practices.